Associations of objectively-assessed physical activity and sedentary time with depression: NHANES (2005-2006) - Vallance, J.; Winkler, E.; Gardiner, P.; Healy, Genevieve; Lynch, B.; Owen, N. (2011)
Background: Studies provide conflicting evidence for the protective effects of moderate-to-vigorous-intensity physical activity on depression. Recent evidence suggests that sedentary behaviors may also be associated with depression. Purpose: To examine the associations of accelerometer-derived moderate-to-vigorous-intensity physical activity and sedentary time with depression among a population-based sample. Methods: Cross-sectional study using 2,862 adults from the 2005-2006 US National Health and Nutrition Examination Survey. ActiGraph accelerometers were used to derive both moderate-to-vigorous-intensity physical activity and sedentary time. Results: Depression occurred in 6.8% of the sample. For moderate-to-vigorous-intensity physical activity, compared with those in quartile 1 (least active), significantly lower odds of depression were observed for those participants in quartiles 2 (OR = 0.55, 95% CI, 0.34 to 0.89), 3 (OR = 0.49, 95% CI, 0.26 to 0.93), and 4 (most active) (OR = 0.37, 95% CI, 0.20 to 0.70) (p for trend p< 0.01). In overweight/obese participants only, those in quartile 4 (most sedentary) had significantly higher odds for depression than those in quartile 1 (least sedentary) [quartile 3 vs 1 (OR = 1.94, 95% CI, 1.01 to 3.68) and 4 vs 1 (OR = 3.09, 95% CI, 1.25 to 7.68)]. Conclusion: The current study identified lower odds of depression were associated with increasing moderate-to-vigorous-intensity physical activity and decreasing sedentary time, at least within overweight/obese adults.